Hydrogen Peroxide Signaling in the Maintenance of Plant Root Apical Meristem Activity - Hui Liu; Yangwei Mu; Yuxin Xuan; Xiaolin Wu; Wei Wang; Hui Zhang (MDPI AG, 2024)
Hydrogen peroxide (H2O2) is a prevalent reactive oxygen species (ROS) found in cells and takes a central role in plant development and stress adaptation. The root apical meristem (RAM) has evolved strong plasticity to adapt to complex and changing environmental conditions. Recent advances have made great progress in explaining the mechanism of key factors, such as auxin, WUSCHEL-RELATED HOMEOBOX 5 (WOX5), PLETHORA (PLT), SHORTROOT (SHR), and SCARECROW (SCR), in the regulation of RAM activity maintenance. H2O2 functions as an emerging signaling molecule to control the quiescent center (QC) specification and stem cell niche (SCN) activity. Auxin is a key signal for the regulation of RAM maintenance, which largely depends on the formation of auxin regional gradients. H2O2 regulates the auxin gradients by the modulation of intercellular transport. H2O2 also modulates the expression of WOX5, PLTs, SHR, and SCR to maintain RAM activity. The present review is dedicated to summarizing the key factors in the regulation of RAM activity and discussing the signaling transduction of H2O2 in the maintenance of RAM activity. H2O2 is a significant signal for plant development and environmental adaptation.